Government Policy Regarding Education in Indonesia: Analysis of Competence-Based Curriculum, Educational Unit Level Curriculum, and Curriculum 2013 - Abidin Nurdin; Sri Astuti A. Samad; Munawwarah Samad; Fakhrurrazi Fakrurrazi (Department of Government Studies, Universitas Syiah Kuala, 2023)
The curriculum is a government policy in the field of education determined by the government. The curriculum has continued to change according to the times and advances in science and technology. This study uses a qualitative method by producing descriptive data as an observable social reality, namely the educational curriculum. The social reality is then analyzed using public policy theory. This article concludes that the curriculum as a political policy from the Indonesian government in the field of education is a logical consequence of social change and development of science. From 1999 to 2013 there were three changes to the curriculum, namely the Competency-Based Curriculum (KBK), the Education Unit Level Curriculum (KTSP) and the 2013 Curriculum (K-13). Each curriculum has its own focus and emphasis point. The purpose of the curriculum changes carried out by the government from a theoretical point of view of public policy is oriented towards fulfilling the needs and interests of the community. So that the curriculum can still be adapted to social changes, scientific and technological developments that occur in society in Indonesia and the wider world